DEM Generation Using Cartosat-I Stereo Data and its Comparison with Publically Available DEM. (2016) - Krishnan, Sooraj; Sajikumar, N.; Sumam, K.S.
Abstract: Cartosat-I or IRS P5 (Indian Remote Sensing Satellite) is a remote sensing satellite meant for cartographic applications like generation of Digital Elevation Model (DEM) and was launched by Inadian Space research organization (ISRO). The paper aims to generate a high quality DEM from Cartosat-I stereo data by means of Leica Photogrammetry Suite (LPS) and thereby comparing the generated DEM with publically available DEMs like ASTER DEM, SRTM DEM and three versions CartoDEMs from NRSC. Results from the study shows that the DEM generated from Cartosat-I stereo data using LPS is more accurate than the publically available Carto DEMs but less accurate than the ASTER and the SRTM DEMs.